2006
DOI: 10.1007/s10751-006-9362-x
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer characterization of calcium–ferrite oxides prepared by calcining Fe2O3 and CaO

Abstract: Calcium ferrite oxides were prepared by calcining a mixture powder of iron-and calcium oxide. The 57 Fe-Mössbauer spectra of the calcium ferrites oxides were measured, revealing that the products should be Ca 2 Fe 2 O 5 and CaFe 2 O 4 , the ratio of which was dependent of the Fe/Ca atomic ratio of the mixture powder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 3 publications
5
25
0
Order By: Relevance
“…With increasing milling time, the sextet becomes asymmetric toward the inside of each line, slowly collapses, and is gradually replaced by a central doublet. This spectral component can be assigned to the CaFe 2 O 4 product [17]; the detailed analysis of Mössbauer data is given below. In this context, it is interesting to note that the Mössbauer spectrum of ␣-Fe 2 O 3 exhibits only a broadened sextet even if the particle size of the material reaches the nanoscale range; i.e., it does not display a superparamagnetic doublet and, thus, unreacted hematite can easily be detected in the Mössbauer spectra [3,13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing milling time, the sextet becomes asymmetric toward the inside of each line, slowly collapses, and is gradually replaced by a central doublet. This spectral component can be assigned to the CaFe 2 O 4 product [17]; the detailed analysis of Mössbauer data is given below. In this context, it is interesting to note that the Mössbauer spectrum of ␣-Fe 2 O 3 exhibits only a broadened sextet even if the particle size of the material reaches the nanoscale range; i.e., it does not display a superparamagnetic doublet and, thus, unreacted hematite can easily be detected in the Mössbauer spectra [3,13].…”
Section: Resultsmentioning
confidence: 99%
“…[16,17]. Nowadays, Ca-Fe-O complex oxides are promising materials for high-temperature electrochemical devices, such as ceramic membranes and electrodes for solid oxide fuel cells [18].…”
Section: Introductionmentioning
confidence: 99%
“…; S -(Mg, Zn) Fe,O^, ZnFe,O,; 6, '7 -(Mg 'Zn) Fe,OT abie 1. Hyperfine parameters of the studied samples »M>»<ï^Tiu>a» obtaining of both ZnFefi^ and D. Hirabayashi et al[33] have shown the possibility of jointly producing two types of calcium ferrite -CaFe^O^ and Ca^Fe^Oj, respectively having doublet and sextet Mossbauer spectrums.…”
mentioning
confidence: 94%
“…[1,2]. In addition, CaFe 2 O 4 shows remarkable physical characteristics, such as high thermal stability, which makes it applicable over a wide temperature range [3].…”
Section: Introductionmentioning
confidence: 99%